Brettanomyces Spoilage in Albanian Wines Assessed by Culture‐Dependent and Culture‐Independent Methods. Issue 3 (29th January 2019) - Lloha, Ilir; Peçuli, Anisa; Basha, Elton; Zejnelhoxha, Sanije; Mamoci, Erjon; Milanović, Vesna; Sabbatini, Riccardo; Osimani, Andrea; Garofalo, Cristiana; Clementi, Francesca; Agarbati, Alice; Ciani, Maurizio; et al.
Abstract : Abstract: In the Albanian winemaking industry, there is little awareness of the potential detrimental effect of Brettanomyces in wines. The aim of this study was to detect and quantify Brettanomyces cells in 22 Albanian bottled wines, representing all the viticultural areas of Albania. A combined approach, including culture‐dependent (viable plate counting) and culture‐independent (qPCR) methods, was applied. Spoilage indicators (ethylphenols and total and volatile acidity), as well as the primary factors known to influence the growth of Brettanomyces in wine (pH, SO2, and ethanol concentration), were also investigated. Brettanomyces was detected in only five (one Merlot, four Sheshi i Zi) out of 22 samples analyzed using viable counting, with loads ranging from 1.30 ± 0.03 log CFU/mL to 3.99 ± 0.00 log CFU/mL, whereas it was never detected in the Kallmet samples. When qPCR was applied, Brettanomyces cells were detected and quantified in all of the samples with a generally low load ranging from 0.47 ± 0.13 to 3.99 ± 0.01 log cells/mL. As a general trend, the loads of spoilage by this yeast were low (≤1.92 log cells/mL), with the exception of five samples that were also positive by plate counting. A positive correlation between the growth of this spoilage yeast on Dekkera / Brettanomyces differential media and its detection at high levels by qPCR was observed. A significant positive correlation between Brettanomyces and the concentration of ethylphenols and volatile acidity was also found. In summary, the results of this study demonstrated the low incidence of Brettanomyces spoilage yeasts in Albanian red wines. Practical Application: The awareness of Brettanomyces spoilage in the Albanian winemaking industry is very low. This study represents the first contribution to understand the extent of this spoilage yeast in Albanian autochthonous cultivars, which tend to have high economic value, to ensure product quality and safety. qPCR is confirmed to be a very sensitive method to rapidly detect Brettanomyces spoilage in wine samples.